PENGARUH KELENGKAPAN PRODUK DAN PERSEPSI KUALITAS TERHADAP LOYALITAS PELANGGAN PRODUK VIVA COSMETICS DI BATAM - Purba, Tiurniari; Heryenzus, Heryenzus (JURSIMA, 2025)
The industrial world is currently progressing very rapidly, this is influenced by technology that is experiencing rapid development. The development of the industry as widely used by business people in running their business. This study aims to analyze the effect of quality perception and product completeness on customer loyalty. The sampling technique is saturated sampling, which means that all populations are sampled in this study. Data processing using SPSS version 25 with quantitative research type. The results of the t-test (partial) that product completeness have a positive and significant effect on customer loyalty with t count > t table with a significance value <0.05 that is 2.845>1.656 and a significant value of 0.000 <0.05, quality perception has a positive and significant effect on customer loyalty with t count > t table with a significance value of <0.05, namely 5.780>1.656 and a significance value of 0.000 <0.05. This is evidenced from the results of the F test where f count>f table with a significance value <0.05, namely 57.545> 2.67 and a significance value of 0.000 <0.05 which states that product completeness and quality perception have a positive and simultaneous significant effect on customer loyalty at the VIVA Cosmetics